Relation of Blood Omentin-1 and Some Biochemical Parameters With Body Mass Index in Patients of Nonalcoholic Fatty Liver Disease - Haneen Hassan Ali; Khalid Shaalan Sahab (Academic Science Journal)
Nonalcoholic fatty liver disease (NAFLD) is a condition of increasing fat in liver of individuals who do not consume significant amount of alcohol. The study aimed to estimate Omentin-1, insulin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALk) , albumin, globulin, total protein, CRP, Triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL) in the serum of NAFLD patients, and find the relationship of variation in omentin-1 and Some Biochemical Parameters with body mass index(BMI) in Patients of NAFLD And comparing them with to the healthy ones. Ninety people were involved in this study (60 were patients with NAFLD and 30 healthy individuals) from Al-Muqdudia General Hospital in Diyala province, Iraq, during the period 1/10/2021 to 30/12/2021. The ELISA Kit was used to detect serum omentin-1. A rapid quantitative assay HS-INSULIN-CHECK-1 is used to estimate the of insulin. The CRP-latex is a slide agglutination test for the quantitive and semi-quantitive detection of C-reacive protein (CRP) in human serum. in serum AST, ALT, ALP, Albumin Globulin, Total Protein, TG, TC and HDL tests were assessed using an Semi automated spectrophotometer (Humalyzer Primus). Serum omentin-1 levels were higher in patients than in healthy subjects with significant differences (p<0.05). Serum levels of ALT , AST and CPR were increased significantly in patients compared with controls (p<0.05). The results ALP, LDL, albumin, total protein, insulin ,and globulin showed no significant increase(p>0.05) in patients compared with controls. Serum cholesterol, TG and VLDL were significantly (p<0.05) elevated in patients in comparison to controls group, while HDL levels were decreased non significantly (p>0.05). Omentin-1 was positively correlated with cholesterol, TG, LDL, VLDL, insulin, ALP and globulin BMI. Serum omentin-1 concentrations were negatively correlated with HDL, ALT, AST, albumin and protein. All these correlations between serum omentin-1 and biochemical parameters were without significant different (p>0.05). The omentin-1 showed not significant association with the anthropometries measurements.